ISLAMISASI ILMU PENGETAHUAN - Moh Hafid (Fakultas Agama Islam Universitas Nurul Jadid, 2021)
An idea emerged to bring together the physical and metaphysical realms. A new science that was modern but still religious in nature and based on monotheism was known as the